2016
DOI: 10.22227/1997-0935.2016.4.108-118
|View full text |Cite
|
Sign up to set email alerts
|

The performance of companies in terms of outsourcing

Abstract: In the article the essence of outsourcing as a new form of employment relations is considered, its features are defined in comparison with traditional forms of employment, its advantages and disadvantages are given. The authors describe the reasons why companies resort to outsourcing, in particular, on the example of small business, illustrate the strategic importance of outsourcing. The practical application of outsourcing is becoming more widespread in the modern business. The scientific and actual role of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The matrixes most commonly used by consulting companies include outsourcing matrix K. Vitasek and M.Ledyard (2013); matrix of outsourcing of Ronan McIvor, Paul K. Humphreys, Anthony Wall, Alan McKittrick (2009); matrix of outsourcing of Mingu Kang, Xiaobo Wu and Paul Hong (2009); Kurbanov's model (Isavnin & Farkhoutdinov, 2013). The study of settlement and economic of outsourcing justification has shown that basically evaluating its effectiveness includes comparison of its own costs and outsourcing costs, which was done in the works of Anikin, Rudaya (2017), Davydkin (2011), Dubrovskaya (2016), Shmigol (2010), Skakun (2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The matrixes most commonly used by consulting companies include outsourcing matrix K. Vitasek and M.Ledyard (2013); matrix of outsourcing of Ronan McIvor, Paul K. Humphreys, Anthony Wall, Alan McKittrick (2009); matrix of outsourcing of Mingu Kang, Xiaobo Wu and Paul Hong (2009); Kurbanov's model (Isavnin & Farkhoutdinov, 2013). The study of settlement and economic of outsourcing justification has shown that basically evaluating its effectiveness includes comparison of its own costs and outsourcing costs, which was done in the works of Anikin, Rudaya (2017), Davydkin (2011), Dubrovskaya (2016), Shmigol (2010), Skakun (2010).…”
Section: Literature Reviewmentioning
confidence: 99%